Meeting report: Salamander models in cross‐disciplinary biological research meeting. Issue 6 (10th May 2022) - Masselink, Wouter; Sandoval‐Guzmán, Tatiana; Yun, Maximina H.
Abstract: The third annual meeting on "Salamander Models in Cross‐disciplinary Biological Research" took place online on August 2021, bringing together over 200 international researchers using salamanders as research models and encompassing diverse fields, ranging from Development and Regeneration through to Immunology, Pathogenesis, and Evolution. The event was organized by Maximina H. Yun (Center for Regenerative Therapies Dresden, Germany) and Tatiana Sandoval‐Guzmán (TU Dresden, Germany) with the generous support of the Deutsche Forschungsgemeinschaft, the Center for Regenerative Therapies Dresden, Technische Universität Dresden, and the Company of Biologists. Showcasing a number of emerging salamander models, innovative techniques and resources, and providing a platform for sharing both published and ongoing research, this meeting proved to be an excellent forum for exchanging ideas and moving research forwards. Here, we discuss the highlights stemming from this exciting scientific event. Key Findings: Summary of the 2021 Salamander meeting. Highlights of key research currently ongoing in various laboratories around the world. Invitation to people to attend the 2022 salamander meeting.